State-of-the-Art Aircraft Icing and Anti-Icing Simulation - Saeed, Farooq (2003)
The paper gives a brief description of the various state-of-the-art mathematical models used to simulate ice accretion and anti-icing simulation on an aircraft wing section. These models are implemented in the CANICE code. CANICE results from a typical icing and anti-icing simulation are presented in comparison with available experimental data and another icing code, LEWICE. The paper also discusses the usefulness of CANICE in reliably predicting ice accretion and in assessing anti-icing heat requirements for given flight and atmospheric conditions. The anti-icing system is modeled after a hot-air jet impinging on a flat plate from which the internal heat transfer coefficients are obtained. The optimum hot-air mass flux needed to avoid icing can be obtained by coupling the CANICE code with an optimization code